Dynamic Capabilities, Internationalization and Growth of Small- and Medium-Sized Enterprises: The Roles of Research and Development Intensity and Collaborative Intensity - Viktor Fredrich; Siegfried Gudergan; Ricarda B. Bouncken (Management International Review, 2022)
Small- and medium-sized enterprises (SMEs) can benefit from internationalization. However, there is little evidence of the extent of the benefit and its dependence on both research and development (R&D) intensity and collaborative intensity. Drawing on data of 262 SMEs, this study illuminates why some SMEs benefit more from internationalization than others, thereby illustrating an advanced application of partial least squares structural equation modeling by demonstrating conditional mediation analysis with two interdependent exogenous moderators (i.e., testing a second-stage three-way conditional mediation). Our findings substantiate that an SME's dynamic capabilities affect its degree of internationalization and indirectly its growth, and suggest a positive marginal growth impact of internationalization provided that an SME's R&D and collaborative intensities are proportional; when they are disproportional (i.e., one is "greater" than the other), SMEs do not experience positive marginal growth.
Keywords: 330; Dynamic capabilities; Internationalization; Growth; SME; R&D intensity; Collaborative intensity; PLS-SEM; Conditional mediation